The Environmental Effects Of Intra-Industry Trade In The SAARC Region - Bilal, Tariq; Rossazana, Ab. Rahim (Universiti Malaysia Sarawak (UNIMAS), 2016)
In the setting of globalization, the rising importance of international financial institutions and international relations as well as the emergence of environmental issues has inspired a new sense of political and economic interaction. Owing to these interactions, mode of trade has changed and it has resulted in the world trade reforms. Therefore, trade of differentiating goods is being appreciated and encouraged in developing economies. In the context of South Asian Association for Regional Cooperation (SAARC), the intra-industry trade is increasingly replacing inter-industry trade. The environmental effects of the aftermath of expansion in intra-industry trade i.e. scale effect, selection effect and technique effects in the SAARC region are to be assessed in this study. The overall results of this study indicate that if intra-industry trade is expanded, it yields positive impacts on the environment. At the one hand, the disintegration of trade induced environmental effects, implies that the scale effect is hazardous for the environment. On the other hand, the trade induced selection and technique effects are beneficial for the environment in the case of SAARC region.